ROLE OF BIOMARKERS IN PATHOGENES OF MALIGNANT REJUVENESCENCE - Yatsenko, L.D. (World of Medicine and Biology, 2014)
Article shows that biomarkers in oncology are genes (oncogenes, tumor-suppressive genes), their protein outputs, hormones and other bioactive outputs and metabolites. Or their content that differ from normal, and characterize the presence of malignant rejuvenescence in organism. Its spreading, difficulty, forecast, sensibility to radial and chemotherapy, sustainability to chemothereapy.
Keywords: biomarkers; cancergenes; genes information